PENGELOLAAN KOMUNIKASI DAN PROMOSI SEKOLAH UNTUK MENGETAHUI PERSEPSI ORANG TUA DALAM MEMILIH SEKOLAH DASAR - AFRIDA YANI (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2018)
ABSTRAK School communication and promotion are important in attracting parents to choose primary school. Management of school communication and promotion affects parents' perceptions. The purpose of this study is to empirically test the management of school communication and promotion that influences the perception of parents in choosing elementary schools in the Permata Gemilang Integrated Islamic Primary School BSD, South Tangerang. This study uses a qualitative approach with triangulation techniques. From the results of this study found, among others, the communication that has been done by the teachers and SDIT Permata Gemilang staff towards the parents of the students is good enough, but parents of students are not satisfied with the communication services carried out by the Foundation and the school promotion has not been maximized so it affect parents' interest in choosing elementary school. Kata Kunci: Promotion, Communication, Perception